The conservation-restoration history of museum collections in Turkey - Erturk, Nevra (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The first practices in the conservation-restoration of museum collections in Turkey began in the nineteenth century with the opening of the Imperial Museum during the Ottoman Empire. Conservation-restoration work on movable cultural property gained momentum at the beginning of the Republican period from 1923 in terms of legal regulations and organisations. The number of museums increased, workshops and laboratories were established, and formal and non-formal training programmes were launched in subsequent years. In this context, our research questions are: What were the improvements in conservation-restoration work on museum collections in the Republican period? Were the scope and quality of conservation-restoration practices in state museums and private museums different from each other in the Republican period? A literature review and personal communication are used as research methods. The article gives information on the history of conservation-restoration work on museum collections; discusses the legal regulations, organisations, experts, workshops, and laboratories; and the procurement of materials and equipment. It concludes with a general evaluation of the nature and extent of conservation-restoration practices of collections in Turkish museums.
Keywords: Conservation-restoration history; Turkish museums; museum collections; movable cultural property; History